(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The purpose of this work was to study the content of anti-inflammatory cytokines interleukin-4 (IL-4) and interleukin-10 (IL-10) in different clinical uveitis course complicated by the optic nerve inflammation. Material and Methods. 132 patients with uveitis complicated by the optic nerve inflammation in the active stage were examined and treated. Anti-inflammatory cytokines (IL-4, IL-10) were determined in the blood serum of all the patients by immunoenzyme method. Results. It was found that the content of interleukin-4 in uveitis complicated by the inflammation of the optic nerve was 2.3 times and interleukin-10 - 2.6 times lower in comparison with control group, respectively (p <0.05). We found that the lower concentration of interleukin-10 in the blood serum correlates with the recurrent uveitis complicated by the inflammation of the optic nerve, as evidenced by the revealed strong inverse correlation (r = -0,7327; p <0,05). Conclusions. It was found, that in the active phase of uveitis complicated by the inflammation of the optic nerve, there was a significant reduction in the content of anti-inflammatory cytokines in the blood compared with the control group: interleukin-4 and interleukin-10. Lower concentration of IL-10 in the blood serum correlates with recurrent disease course.